Evaluating Community Resilience and Associated Factors One Year after the Catastrophic Fort McMurray Flood - Gloria Obuobi-Donkor; Ejemai Eboreime; Reham Shalaby; Belinda Agyapong; Medard K. Adu; Ernest Owusu; Wanying Mao; Folajinmi Oluwasina; Hannah Pazderka; Vincent I. O. Agyapong (International Journal of Environmental Research and Public Health, 2022)
Background: Resilience after natural disasters is becoming an increasingly key area of research. In April 2020, parts of Fort McMurray were affected by severe floods. The flooding caused the loss of properties, evacuation of some residents, and effects on their mental health. Objective: This study explores the prevalence and associated factors between flood experience and low resilience a year after the 2020 floods in Fort McMurray. Method: Data collection was accomplished one year after the flood, from 24 April to 2 June 2021, using an online survey. The data were analyzed with SPSS version 25 using univariate analysis with the chi-squared test and binary logistic regression analysis. Results: The prevalence of low resilience was 37.4%. Respondents under 25 years were nearly 26 times more likely to show low resilience (OR = 0.038; 95% CI 0.004–0.384) than respondents 40 years and above. Responders with a history of depression (OR = 0.258 95% CI: 0.089–0.744) and a history of anxiety (OR = 0.212; CI 95% 0.068–0.661) were nearly four to five times more likely to show low resilience than those without a history. Similarly, respondents willing to receive mental health counselling (OR = 0.134 95% CI: 0.047–0.378) were 7.5 times more likely to show low resilience. Participants residing in the same house before the flood were almost 11 times more likely to show low resilience (OR = 0.095; 95% CI 0.021–0.427) than those who relocated. Participants who received support from the Government of Alberta were less likely to express low resilience than those who received no or limited support (OR = 208.343; 95% CI 3.284–13,218.663). Conclusion: The study showed a low resilience rate among respondents following the 2020 flooding in Fort McMurray. Factors contributing to low resilience include age, history of depression or anxiety, and place of residence after the flood. After the flood, receiving support from the government was shown to be a protective factor. Further studies are needed to explore robust risk factors of low ...